2006
DOI: 10.1097/01.brs.0000238977.36165.b8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Scheuermann Kyphosis Correction by Posterior-Only Thoracic Pedicle Screw Fixation Versus Combined Anterior/Posterior Fusion

Abstract: With less operating time and intraoperative blood loss, posterior-only Scheuermann kyphosis treatment with thoracic pedicle screws achieved and maintained better correction, and had significantly less complications than with circumferential fusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
71
0
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(90 citation statements)
references
References 17 publications
7
71
0
12
Order By: Relevance
“…With most patients having LIV at the first-lordotic disc in our study, the number of levels fused could be limited to eight on average, indicating a mobile lumbar spine in most patients. In other studies, fusion length averaged 11 [36], 12 [29] and 13 levels [28] or was not reported [3,8]. There is ongoing discussion regarding the appropriate end level to spare motion segments while lowering the risk of PJK and DJK [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With most patients having LIV at the first-lordotic disc in our study, the number of levels fused could be limited to eight on average, indicating a mobile lumbar spine in most patients. In other studies, fusion length averaged 11 [36], 12 [29] and 13 levels [28] or was not reported [3,8]. There is ongoing discussion regarding the appropriate end level to spare motion segments while lowering the risk of PJK and DJK [37].…”
Section: Discussionmentioning
confidence: 99%
“…In our review of literature (Table 2) which included a total of 727 patients, with an average sample size of 29 and mean age of 20 years, three studies reported on clinical outcomes using validated measures. Flexibility data were reported only by Koptan (in %) [23], Lee (in %) [29], Johnston (in %) [36], Herera-soto (in°) [28] and Hosman (in°) [8]. There has been no study yet comparing both strategies based on comparable preoperative kyphosis and flexibility in a sufficiently large sample.…”
Section: Discussionmentioning
confidence: 99%
“…No primeiro grupo, o grau médio de correção foi de 52%, após seguimento médio de 31,7 meses, enquanto no segundo grupo de pacientes a média foi de 54,6%, após seguimento médio de 67,5 meses. Dos 18 pacientes do primeiro grupo, nove tiveram complicações, enquanto oito dos 21 pacientes do segundo grupo apresentaram complicações como cifose funcional proximal e distal, paraplegia imediatamente após o procedimento posterior, tendo-se procedido à retirada emergencial do material (18) .…”
Section: Discussionunclassified
“…Therefore, we opted to use a sample projected to a work of greater international importance, involving 39 patients, which was conducted partly retrospectively and partly prospectively, and published in 2006 by Lee et al (20) . Our sample consisted of 28 patients, divided into two groups, and operated at different times.…”
Section: Methodsmentioning
confidence: 99%